Cur homo deus? Some considerations regarding the right to life - Thomas Mertens (Ethic@: an International Journal for Moral Philosophy)
One of the most important rights humans have is the right to life. But its status is far from self-evident. This paper raises a few questions regarding this right: what does it mean conceptually, and what does it imply; what is its status within a catalogue of fundamental rights; who is the owner of the right to life, and does it include the right to die? In connection with present legal developments, it is asked whether the right to self-determination should be given priority over the right to life, as was suggested by a recent decision by the German constitutional court.